2011
DOI: 10.2174/157489211795328477
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapies in the Treatment of Locally Advanced Squamous Cell Cancers of Head and Neck

Abstract: Head and neck squamous cell cancers (HNSCCs) represent 4 to 5% of all solid malignancies. Despite improvements in diagnostic techniques, 60% of patients will present with locally advanced HNSCCs with a median survival of about 12 months and 5-year overall survival of approximately 10-40%. Recent clinical trials have altered the treatment landscape by refining existing forms of radiation, incorporation of IMRT, choice of chemotherapeutic agents, introduction of biological and targeted therapy, immunotherapy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Activated EMT signaling pathways (e.g., activation of Wnt/β-catenin, PI3-K/AKT, MAPK, and Notch) is well documented to occur in advanced OCC (Boyer et al, 2000; Conacci-Sorrell et al, 2002; Nelson and Nusse, 2004; Larue and Bellacosa, 2005; Nawshad et al, 2005; Tommasi et al, 2007; Barker, 2008; Agarwal et al, 2010; Courtney et al, 2010; Falasca, 2010; Ihle and Powis, 2010; Wong et al, 2010). Preclinical studies also reported a significant correlation between EMT phenotype, drug resistance, and relapses (Zeisberg and Neilson, 2009) including in OCC patients (Machiels and Schmitz, 2011; Raza et al, 2011). …”
Section: Emt and Csc Concepts And Their Impact On Drug Resistancementioning
confidence: 95%
“…Activated EMT signaling pathways (e.g., activation of Wnt/β-catenin, PI3-K/AKT, MAPK, and Notch) is well documented to occur in advanced OCC (Boyer et al, 2000; Conacci-Sorrell et al, 2002; Nelson and Nusse, 2004; Larue and Bellacosa, 2005; Nawshad et al, 2005; Tommasi et al, 2007; Barker, 2008; Agarwal et al, 2010; Courtney et al, 2010; Falasca, 2010; Ihle and Powis, 2010; Wong et al, 2010). Preclinical studies also reported a significant correlation between EMT phenotype, drug resistance, and relapses (Zeisberg and Neilson, 2009) including in OCC patients (Machiels and Schmitz, 2011; Raza et al, 2011). …”
Section: Emt and Csc Concepts And Their Impact On Drug Resistancementioning
confidence: 95%
“…Our main goals are to find specific biomarkers for discriminating different types of OPSCC (HPV active and negative) and to propose potential targeted therapies specific for each group. Considering these two groups (HPV‐active and HPV‐negative), our study will focus only on biological processes underlying the “distinction” of the specified groups (and therefore giving insight to targeted therapy of OPSCC subtypes based on HPV activity); for example, EGFR or PI3K/AKT pathways, which are known as two important pathways (and therefore targets for therapies) in the pathogenesis of head and neck cancers, are not highlighted in our analysis because their behavior has not been observed to be significantly different in these groups . This study is composed of two main analyses: gene co‐expression network analysis and consensus network analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Other targeted therapies remain under investigation in HNC, including antiangiogenic agents, PI3K/Akt/mTor inhibitors, and p53 gene replacement therapy. 58−60 Whereas such targeted approaches have certainly benefited some patients, their overall impact on HNC treatment has been mixed, 59−62 and personalized or combination therapy will likely prove necessary to maximize clinical success of these targeted drugs; 60,61 thus, more effective general first-line chemotherapy treatments are still much needed. Given the limited but promising data on the potential of MTAs in HNC, appropriate disease models therefore represent a useful context for the testing and development of new agents in the class.…”
Section: ■ Introductionmentioning
confidence: 99%